Three-dimensional honeycomb-like porous carbon derived from corncob for the removal of heavy metals from water by capacitive deionization. Issue 3 (4th January 2018) - Zhang, X. F.; Wang, B.; Yu, J.; Wu, X. N.; Zang, Y. H.; Gao, H. C.; Su, P. C.; Hao, S. Q.
Abstract : A porous carbon electrode with a 3D honeycomb-like structure demonstrates a high removal efficiency for the removal of chromium(vi ) from water. Abstract : In this study, porous carbon (3DHPC) with a 3D honeycomb-like structure was synthesized from waste biomass corncob via hydrothermal carbonization coupled with KOH activation and investigated as a capacitive deionization (CDI) electrode material. The obtained 3DHPC possesses a hierarchal macroporous and mesoporous structure, and a large accessible specific surface area (952 m 2 g −1 ). Electrochemical tests showed that the 3DHPC electrode exhibited a specific capacitance of 452 F g −1 and good electric conductivity. Moreover, the feasibility of electrosorptive removal of chromium(vi ) from an aqueous solution using the 3DHPC electrode was demonstrated. When 1.0 V was applied to a solution containing 30 mg L −1 chromium(vi ), the 3DHPC electrode exhibited a higher removal efficiency of 91.58% compared with that in the open circuit condition. This enhanced adsorption results from the improved affinity between chromium(vi ) and the electrode under electrochemical assistance involving a non-faradic process. Consequently, the 3DHPC electrode with typical double-layer capacitor behavior is demonstrated to be a favorable electrode material for capacitive deionization.